HUMANIZATION OF CHARACTER EDUCATION IN ELEMENTARY SCHOOLS: FENOMOLOGY STUDY OF INCLUSIVE LEARNING BASED ON ISLAMIC VALUES - Sarah Lady Diana Islamy; Ahmad Hafidz Lubis; Haidar Idris (International Conference on Humanity Education and Society (ICHES), 2026)
Character education in elementary schools has tended to be understood as a process of normative and cognitive value instillation, so that the human aspects of students often receive little attention. This phenomenon is also found in educational practices in several elementary schools in Lumajang Regency, where character learning still focuses on obedience and formal behavioral achievements, while the needs for inclusiveness and a humanistic approach have not been fully internalized. This study aims to reveal the meaning and form of humanization of character education in the practice of inclusive learning based on Islamic values in elementary schools. The study uses a qualitative approach with a phenomenological method, involving elementary school teachers as the main subjects through in-depth interviews and learning observations. The results show that the humanization of character education is realized through empathetic pedagogical relationships, appreciation of student diversity, and the integration of Islamic values such as compassion, justice, and responsibility in daily learning practices. These findings expand on previous research that emphasized the normative aspects of character education, offering a phenomenological perspective on teachers' experiences in building inclusive and humanistic character education. This study concludes that a humanization approach based on Islamic values has the potential to strengthen character development and inclusive human development at the elementary school level.